2019
DOI: 10.1111/jfb.13988
|View full text |Cite
|
Sign up to set email alerts
|

Environmental niche patterns of native and non‐native fishes within an invaded African river system

Abstract: To test ecological niche theory, this study investigated the spatial patterns and the environmental niches of native and non-native fishes within the invaded Great Fish River system, South Africa. For the native fishes, there were contrasting environmental niche breadths that varied from being small to being large and overlapped for most species, except minnows that were restricted to headwater tributaries. In addition, there was high niche overlap in habitat association among fishes with similar distribution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Consistent with previous research and studies elsewhere (e.g. Kadye & Booth, 2020;Schmidt et al, 2019), it is likely that the anthropogenic modification of this river system, particularly through altered flow, may have resulted in a functional assemblage that has acclimatized to these conditions. This assemblage appears to largely reflect ichthyofauna groups with shared functional traits in different invaded sections, including the tributaries where non-native T. sparrmanii co-occurs with native species and the upper and lower mainstem sections where most non-native species co-occur with native species.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with previous research and studies elsewhere (e.g. Kadye & Booth, 2020;Schmidt et al, 2019), it is likely that the anthropogenic modification of this river system, particularly through altered flow, may have resulted in a functional assemblage that has acclimatized to these conditions. This assemblage appears to largely reflect ichthyofauna groups with shared functional traits in different invaded sections, including the tributaries where non-native T. sparrmanii co-occurs with native species and the upper and lower mainstem sections where most non-native species co-occur with native species.…”
Section: Discussionsupporting
confidence: 85%
“…This is because, in addition to altering the physico‐chemical conditions of the recipient ecosystems, mainly through changing their natural flow regime, IBWTs may inadvertently facilitate species translocations and successful establishments of non‐native taxa into new environments (Ellender & Weyl, 2014; Laurenson & Hocutt, 1985). Often, IBWTs facilitate translocations of more than one species, thereby promoting co‐occurrences of multiple non‐native species, which raises concern over their potential impact within the invaded systems (e.g., Kadye & Booth, 2020; Laurenson & Hocutt, 1985; Nagelkerke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instream habitats and flow have been variously altered because of construction of weirs and dams, agricultural activities and invasion of the catchments by non‐native plants, particularly black wattle Acacia mearnsii De Wild. Non‐native fishes have also been introduced into the Kat River Dam located in the upper section of the Kat River and the lower sections of the Kat and Koonap rivers (Kadye & Booth, 2020; Laurenson & Hocutt, 1986).…”
Section: Methodsmentioning
confidence: 99%
“…(2020) described upstream movements of up to 397 km by tigerfish Hydrocynus vittatus Castelnau 1861 and used information on their movement ecology to assess the feasibility of freshwater protected areas as a conservation tool. Kadye and Booth (2020) examined the degree of environmental niche overlap between native and non‐native fish species in the invaded Great Fish River system in South Africa. These authors concluded that environmental alterations are likely to create conditions that are favourable to the establishment and proliferation of introduced species, which in turn increases the risk of negative interactions with native species.…”
mentioning
confidence: 99%